2022
DOI: 10.1177/17455057221091732
|View full text |Cite
|
Sign up to set email alerts
|

Continuum of maternal healthcare services utilization and its associated factors in Ethiopia: A systematic review and meta-analysis

Abstract: The continuum of care throughout pregnancy, childbirth, and postnatal period is one of the vital strategies for improving maternal and neonatal health and preventing maternal and neonatal mortalities and morbidities. The level and determinants of the complete continuum of care for maternal health services reported by different studies were extremely varied in Ethiopia. Therefore, this meta-analysis aimed to estimate the overall prevalence of a complete continuum of maternal health care services utilization and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 48 publications
1
18
0
Order By: Relevance
“…In this study overall ANC 1, ANC 4, skilled birth attendance, and postnatal care utilization is 74.9%, 43.5%, 51.9%, and 32.0%, respectively. A systematic review reported that only a quarter (25.5%) of the women in had used a complete continuum of care (at least four ANC visits, skilled birth attendant, and at least one PNC within 6 weeks after delivery) in Ethiopia [15]. Another systematic review reported that 64%, 31%, and 32% of women in Ethiopia utilized ANC, institutional delivery, and PNC service, respectively [16,18,19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study overall ANC 1, ANC 4, skilled birth attendance, and postnatal care utilization is 74.9%, 43.5%, 51.9%, and 32.0%, respectively. A systematic review reported that only a quarter (25.5%) of the women in had used a complete continuum of care (at least four ANC visits, skilled birth attendant, and at least one PNC within 6 weeks after delivery) in Ethiopia [15]. Another systematic review reported that 64%, 31%, and 32% of women in Ethiopia utilized ANC, institutional delivery, and PNC service, respectively [16,18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Amwonya et al also reported that female education indeed had a positive impact on maternal health care utilization [14]. A review study in Ethiopia also revealed that educational status is associated with a higher likelihood of having a continuum of maternal healthcare services [15].…”
Section: Introductionmentioning
confidence: 95%
“…Previous research has found socioeconomic and demographic factors such as education and wealth status as being important predictors for accessing care across the continuum in Indonesia (Nafiah et al ., 2022 ; Andriani et al ., 2022 ) and in other lower- and middle-income countries (Osaki et al ., 2013 ; Yeji et al ., 2015 ; Wang and Hong, 2015 ; Iqbal et al ., 2017 ; Addisu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“… 9 , 22 - 27 However, in many societies, cultural beliefs and lack of awareness inhibit preparation in advance for delivery. 28 , 29 In Ethiopia, a systematic review and meta-analysis showed that the utilization of maternal health care services was low, which is 25.51%, 30 and the BPCR was also low, which is 32%. 4 Having a good practice of the BPCR plan increases the utilization of maternal health care services.…”
Section: Introductionmentioning
confidence: 99%